Centers of excellence in healthcare institutions: what they are and how to assemble them - James K. Elrod; John L. Fortenberry (BMC, 2017)
Abstract Background Centers of excellence-specialized programs within healthcare institutions which supply exceptionally high concentrations of expertise and related resources centered on particular medical areas and delivered in a comprehensive, interdisciplinary fashion-afford many advantages for healthcare providers and the populations they serve. To achieve full value from centers of excellence, proper assembly is an absolute necessity, but guidance is somewhat limited. This effectively forces healthcare providers to pursue establishment largely via trial-and-error, diminishing opportunities for success. Discussion Successful development of a center of excellence first requires the acquisition of a detailed understanding of the delivery model and its benefits. Then, concerted actions must be taken on a particular series of administrative and clinical fronts, treating them in prescribed manners to afford synergies which yield an exceptionally high level of care. To reduce hardships associated with acquiring this rather elusive knowledge, remedy shortcomings in the literature, and potentially bolster community health broadly, this article presents information and insights gleaned from Willis-Knighton Health System's extensive experience assembling and operating centers of excellence. This work is intended to educate and enlighten, but most importantly, supply guidance which will permit healthcare establishments to replicate noted processes to realize their own centers of excellence. Conclusions Centers of excellence have the ability to dramatically enhance the depth and breadth of healthcare services available in communities. Given the numerous mutual benefits afforded by this delivery model, it is hoped that the light shed by this article will help healthcare providers better understand centers of excellence and be more capable and confident in associated development initiatives, affording greater opportunities for themselves and their patient populations.